LEARNING ABOUT CANNABIDIOL: THE MEDICINAL USE OF CANNABIS SATIVA COMPONENTS - Carlos Leopoldo Pinheiro Muniz, Janailton (Health and Society, 2023)
Alzheimer’s Disease (AD) has different stages and different levels of mental and physical health impairment, which do not cause hospitalization. Thus, we present a manual of procedures for care at the patient’s home, where the caregiver’s role is very important. Physiotherapeutic intervention in patients with AD, linked to Medicine, should take place in a preventive way to the deficiencies that occur due to the lack of physical activities that progressively deteriorate the functional capacity; physiotherapy is indicated in the case of patients with AD, because early treatment has the preventive nature of complications and minimization of symptoms that accompany the pathology in people of advanced age. The general objective is to evaluate and analyze the perspectives in the medical treatment of AD, aiming at its quality of life.